Quality of Inclusive Educational System for Work with Students with Autism Different Needs in Italy - Voitkāne, Vita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The need for realization of inclusive education, which is the basis of a sustainable education, will require new challenges in the Education System. The system used in Italy can be used as an example. Italy passed avant-garde laws concerning the integration and inclusion of special needs students into the general school system already more than thirty years ago, in the 1970s. However, even after all this time and experience, there are still unresolved problems, which testifies to the complexities of the matter. This research offers an insight into the quality of the existing Italian inclusive education system specifically in relation to students with autism. Thereby it hopes to provide educators in Latvia with food for thought about this currently important topic.